1982
DOI: 10.1111/j.1399-3054.1982.tb06330.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical changes associated with cotton fibre development

Abstract: Growth kinetics and levels of auxin substances were studied in three cotton cultivars, designated as long, medium and short staple cultivars. Fibre length and dry weight plotted against boll age showed sigmoidal patterns and were fitted to a logistic curve by computer curvilinear regression analysis. The final length of the fibre in different cultivars was the product of the rate of elongation per day and the total period of elongation. Further, considerable overlap between the elongation and the secondary thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…1b). Growth analysis of cotton fiber, with respect to its length and dry weight, has been reported earlier from this laboratory (Jasdanwala et al 1977, Naithani et al 1982, Thaker et al 1986. In all of these studies it was shown that the development of cotton fiber can be divided into four distinct phases: initiation, elongation, secondary thickening, and maturation, and that there was a clear-cut overlap between various phases.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1b). Growth analysis of cotton fiber, with respect to its length and dry weight, has been reported earlier from this laboratory (Jasdanwala et al 1977, Naithani et al 1982, Thaker et al 1986. In all of these studies it was shown that the development of cotton fiber can be divided into four distinct phases: initiation, elongation, secondary thickening, and maturation, and that there was a clear-cut overlap between various phases.…”
Section: Resultsmentioning
confidence: 96%
“…Considerable evidence indicates that phytohormones play a decisive role in fiber development (Beasley and Ting 1973, 1974, Naithani et al 1982. In in vitro culture of ovules it was observed that indoleacetic acid (IAA) plays an important role in fiber development, whereas abscisic acid (ABA) inhibits it (Beasley and Ting 1973).…”
mentioning
confidence: 99%
“…Dehydration of the cellulosic unit leads to the formation of the double-bonded intermediates [34]. The mass change in fibres starts by lowering the molecular weight [35] and may result in consequently low tensile strength [36]. For temperatures below 300°C, the decomposition proceeded very slowly with only 5 wt.% losses.…”
Section: Thermo-gravimetric Analysis (Tga)mentioning
confidence: 99%
“…Cotton fibers are single-celled seed trichomes that originate from the outer epidermal layer of ovules [1,2]. These single fiber cells, developing synchronously, elongate dramatically after anthesis and finally attain lengths 1000-to 3000-fold greater than their diameters [3].…”
Section: Introductionmentioning
confidence: 99%